2010
DOI: 10.1080/14767333.2010.518378
|View full text |Cite
|
Sign up to set email alerts
|

Reflections and learning from using action learning sets in a healthcare education setting

Abstract: Wood (2010) Reflections and learning from using action learning sets in a healthcare education setting, Action Learning: Research and Practice, 7:3, 303-314,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Action learning can be powerful and frightening (Marsick and O'Neil, 1999) therefore necessitating the crafting of a trusted and safe space. When participants feel unsafe or sense a risk attached to disclosure, learning can be inhibited and opportunities missed (Dunphy et al, 2010). The requirement for trust and safety in action learning supports, and has the ability to enhance, learning (Edmondson and Lei, 2014).…”
Section: Relational Processes Within Action Learning Setsmentioning
confidence: 99%
See 2 more Smart Citations
“…Action learning can be powerful and frightening (Marsick and O'Neil, 1999) therefore necessitating the crafting of a trusted and safe space. When participants feel unsafe or sense a risk attached to disclosure, learning can be inhibited and opportunities missed (Dunphy et al, 2010). The requirement for trust and safety in action learning supports, and has the ability to enhance, learning (Edmondson and Lei, 2014).…”
Section: Relational Processes Within Action Learning Setsmentioning
confidence: 99%
“…The requirement for trust and safety in action learning supports, and has the ability to enhance, learning (Edmondson and Lei, 2014). The potentially challenging nature of action learning can lead to uncomfortableness (Dunphy et al, 2010) and insightful questioning inherent in the action learning process can be an emotional process where emotions such as anger, anxiety, fear, surprise and, at times, joy can be triggered. O'Hara et al (1996: 18) discuss the 'anxiety' that can be experienced and Dunphy et al (2010: 307) found 'the level of self-disclosure' required in the process can generate discomfort.…”
Section: Relational Processes Within Action Learning Setsmentioning
confidence: 99%
See 1 more Smart Citation